Hepatico-Duodenal Fistula Following Iatrogenic Strasberg Type E4 Bile Duct Injury: A Case Report - Bozhidar Hristov; Daniel Doykov; Desislav Stanchev; Krasimir Kraev; Petar Uchikov; Gancho Kostov; Siyana Valova; Eduard Tilkiyan; Katya Doykova; Mladen Doykov (Medicina, 2023)
Introduction: Gallstone disease (GSD) is among the most common disorders worldwide. Gallstones are established in up to 15% of the general population. Laparoscopic cholecystectomy (LC) has become the “gold standard” for treatment of GSD but is associated with a higher rate of certain complications, namely, bile duct injury (BDI). Biliary fistulas (BF) are a common presentation of BDI (44.1% of all patients); however, they are mainly external. Post-cholecystectomy internal BF are exceedingly rare. Case report: a 33-year Caucasian female was admitted with suspected BDI after LC. Strasberg type E4 BDI was established on endoscopic retrograde cholangiopancreatography (ERCP). Urgent laparotomy established biliary peritonitis. Delayed surgical reconstruction was planned and temporary external biliary drains were positioned in the right and left hepatic ducts. During follow-up, displacement of the drains occurred with subsequent evacuation of bile through the external fistula, which resolved spontaneously, without clinical and biochemical evidence of biliary obstruction or cholangitis. ERCP established bilio-duodenal fistula between the left hepatic duct (LHD) and duodenum, with a stricture at the level of the LHD. Endoscopic management was chosen with staged dilation and stenting of the fistulous tract over 18 months until fistula maturation and stricture resolution. One year after stent extraction, the patient remains symptom free. Discussion: Management of post-cholecystectomy BDI is challenging. The optimal approach is determined by the level and extent of ductal lesion defined according to different classifications (Strasberg, Bismuth, Hannover). Type E BDI are managed mainly surgically with a delayed surgical approach generally deemed preferable. Only three cases of choledocho-duodenal fistulas following LC BDI currently exist in the literature. Management is controversial, with expectant approach, surgical treatment (biliary reconstruction), or liver transplantation being described. Endoscopic treatment has not been described; however, in the current paper, it proved to be successful. More reports or larger case series are needed to confirm its applicability and effectiveness, especially in the long term.